2001
DOI: 10.1046/j.1365-2672.2001.01226.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cell envelope-associated proteinases of thermophilic lactobacilli

Abstract: S O J E V I C , I . S T R A H I N I C A N D L . T O P I S I R O V I C . 2001.The proteolytic activities of two natural isolates of thermophilic lactobacilli, Lactobacillus acidophilus BGRA43 and Lact. delbrueckii BGPF1, and Lact. acidophilus CH2 (Chr. Hansen's strain) and Lact. acidophilus V74 (Visby's strain), were compared. Results revealed that optimal pH for all four proteinases is 6á5, whereas temperature optimum varied among proteinases. Determination of caseinolytic activity done under optimal condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
2
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 26 publications
5
37
2
1
Order By: Relevance
“…In the current study, the optimum pH was pH 7.0 (Table 4) and decreased towards the acidity. These findings agreed with Fira, [39], Kabadjova-Hristova [33], and El-Ghaish et al [38], with some variations but with the same trend. The variations might be due to the difference in bacterial species.…”
Section: E Phsupporting
confidence: 89%
“…In the current study, the optimum pH was pH 7.0 (Table 4) and decreased towards the acidity. These findings agreed with Fira, [39], Kabadjova-Hristova [33], and El-Ghaish et al [38], with some variations but with the same trend. The variations might be due to the difference in bacterial species.…”
Section: E Phsupporting
confidence: 89%
“…The cell-enveloped proteases and different intracellular peptidases result in an efficient breakdown of casein, major milk protein, into different amino acids and peptides required for cell growth [17,28]. Several studies reported pH and temperature dependence of the protease activity of several thermophilic LAB species [1,4]. The high proteolytic activity of a β-gal preparation could be undesirable during lactose hydrolysis in milk since it may result in bitterness [19] as well as the digestion of the β-gal enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…However, constitutive and inducible expression systems generally led to the production of microgram-level amounts of recombinant protein per liter of culture (1,2,18). We examined the potential of L. bulgaricus PrtB proteinase to serve as a protein carrier for a foreign sequence because (i) it is a large protein (1,947 amino acids) most likely prone to sustain changes in its primary structure and (ii) it is constitutively expressed at high levels on the surface of L. bulgaricus (5). Successful expression was achieved in L. lactis, as shown by the surface display and release in the supernatant of the heterologous proteinase.…”
Section: Discussionmentioning
confidence: 99%